2018
DOI: 10.1007/s11136-018-2020-3
|View full text |Cite
|
Sign up to set email alerts
|

Making a picture worth a thousand numbers: recommendations for graphically displaying patient-reported outcomes data

Abstract: This is a repository copy of Making a picture worth a thousand numbers: recommendations for graphically displaying patient-reported outcomes data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 14 publications
2
98
0
1
Order By: Relevance
“…Whereas line graphs and pie charts seemed to result in better cognitive and affective outcomes, these results were only based on one significant result each. While a previous review in general health care [8] recommends using icon arrays or bar charts to display outcome information, recent studies on the display of HRQL information specifically, suggested using pie charts [44,45]. Another issue is the direction of display of HRQL data when using bar or line graphs.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas line graphs and pie charts seemed to result in better cognitive and affective outcomes, these results were only based on one significant result each. While a previous review in general health care [8] recommends using icon arrays or bar charts to display outcome information, recent studies on the display of HRQL information specifically, suggested using pie charts [44,45]. Another issue is the direction of display of HRQL data when using bar or line graphs.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Conversely, a panel of experts in a third article recommended line graphs for longitudinal data. 56 Metaphorical icons increased comprehension in some cases 57 but not when patients interpreted them too literally. For example, patients in one study interpreted icons of fruit baskets, intended to represent the number of fruit servings they had consumed, to mean they consumed each of the illustrated fruits.…”
Section: Characteristics Of Articles With Human Patients Researchmentioning
confidence: 97%
“…62 Several articles showed that inclusion of contextual information in visualizations (e.g., reference ranges and explanatory text), especially when personalized, also improves objective comprehension. 45,46,[55][56][57][58]60 Although these components are also helpful for patients interpreting medium risk clinical scenarios and borderline test results, these scenarios remained the most challenging for patients to interpret. 47,63 The only study measuring a clinical outcome reported a trend of decreasing blood glucose and hemoglobin A1c levels over 3 months among participants who completed a webbased self-monitoring intervention that included line graphs of blood glucose over time.…”
Section: Characteristics Of Articles With Human Patients Researchmentioning
confidence: 99%
“…Additional initiatives include PROTEUS Consortium (Patient-Reported Outcomes Tools: Engaging Users & Stakeholders) [49], which aims to promote the uptake and use of tools to support high quality PRO trial data including tools such as: SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) PRO-Extension [12]; ISOQOL (International Society for Quality of Life Research) Minimum Standards for PRO Measures in patient-centered outcomes and comparative effectiveness research [50]; SISAQOL (Setting International Standards in Analysing Patient-Reported Outcomes and Quality of Life Endpoints Data) [51]; CONSORT (Consolidated Standards of Reporting Trials) PRO-Extension [52] Stakeholder-Driven, Evidence-Based Standards for Presenting PROs in Clinical Practice [53]; and Clinician's Checklist for Reading and Using an Article About PROs However, greater work needs to be done to capture PRO data in a rigorous efficient way across disciplines. Furthermore, key societies like Macmillan Cancer Support, ASCO and the NCRI are working on the endorsement of the dissemination of PRO trial studies, which might help to have a wider reach for spreading PRO trial results and consequently a further impact [54,55].…”
Section: Discussionmentioning
confidence: 99%